Variability, Correlation and Path Analysis in F2 Progenies of Inter-Varietal Crosses of Brassica Rapa (Journal of Environmental Science and Natural Resources, 2015)
Eight F2 populations generated through inter-varietal crosses, along with three check varieties of Brassica rapa were evaluated to study the variation in different characters, correlation between pairs of different characters and the direct and indirect effect of different characters on seed yield per plant to select the plants with higher yield potential. From the values of mean, range and (CV%) of seed yield and yield contributing characters it was confirmed that there were considerable variation present among all the genotypes used in the experiment. The values of phenotypic variances were higher than the cor responding genotypic variances. Number of branches per plant, length of siliqua, seeds per siliqua, 1000 seed weight and yield per plant showed least difference between phenotypic and genotypic variances. The values of GCV and PCV indicated that there was least variation present among most of the characters studied. The number of branches per plant, days to 50% flowering, days to maturity and length of siliqua had showed high heritability with low genetic advance and genetic advance in percentage of mean. Yield per plant had significant and highest positive correlation with plant height, days to 50% maturity, length of siliqua and seeds per siliqua. The path co-efficient analysis revealed that siliqua per plant had the highest positive direct effect followed by seeds per siliqua, length of siliqua and plant height. Sixteen most promising plants with higher yield were selected for cultivation.DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22068 J. Environ. Sci. & Natural Resources, 6(1): 217-220 2013